Ethnic Conflict and International Politics - Steven E. Lobell (Palgrave, 2004)
Combining theoretical analyzes with case studies, this book increases understanding of the internationalization, diffusion and escalation of ethnic conflict. The essays stand at the nexus of comparative politics and international relations, examining the influence on ethnic conflict of the weakening of state institutional structures, the role of non-state regional and international actors, changes in the ethnic balance of power, and the degree of economic, social, and cultural integration within the regional or global system. The variety of approaches provides useful analytical tools for students, while the diversity of cases from different regions gives the reader a sense of the scope of such problems.